Piloting a Web-based Practicum Support Tool: Associate Teachers’ Perceived Benefits and Drawbacks - Petrarca, Diana (Alberta Journal of Educational Research, 2015)
This pilot study explored how a small group of associate teachers responded to a web-based learning tool created specifically to support them in mentoring teacher candidates during the practicum component of an initial teacher education program in Southern Ontario, Canada. The learning tool's content drew from the teacher education literature, and its development was grounded in constructivist learning theory, web-based learning literature, and reflective practice. Associate teachers found the learning tool flexible, convenient, easy to use, and although they appreciated the non-directive nature of the learning tool, finding time to access and interact with the tool proved challenging. Associate teachers benefited from accessing and interacting with the learning tool, to varying degrees depending on their prior experiences, with improving feedback processes and practices, supporting teacher candidate planning processes, and facilitating teacher candidate induction emerging as three key areas of enhanced understanding and practice. Two key drawbacks of the learning tool included lack of human interaction, and sufficient time to interact with the learning tool more deeply. Cette étude pilote s’est penchée sur la réaction d’un petit groupe d’enseignants associés travaillant dans le sud de l’Ontario, au Canada, face à un outil d’apprentissage électronique conçu spécifiquement pour les appuyer dans leur mentorat de stagiaires. Le contenu de l’outil d’apprentissage est tiré de publications sur la formation des enseignants, et son développement repose sur la théorie d’apprentissage constructiviste, la documentation d’apprentissage en ligne et la pratique réflexive. Les enseignants associés ont trouvé l’outil d’apprentissage souple, pratique et facile d’emploi. Ils ont apprécié la nature non directive de l’outil d’apprentissage, mais ont signalé qu’ils avaient éprouvé de la difficulté à trouver le temps d’accéder à l’outil et d’interagir avec celui-ci. Les enseignants associés ont profité de l’accès à l’outil et de l’interaction avec celui-ci, à divers degrés en fonction de leurs expériences préalables. Les trois domaines clés où les connaissances et la pratique se sont améliorées sont les suivants : de meilleurs pratiques et processus de rétroaction, un soutien accru aux processus de planification des étudiants en pédagogie et une intégration facilitée des étudiants en pédagogie. Deux inconvénients principaux de l’outil d’apprentissage se sont manifestés, notamment l’absence d’interaction humaine et un manque de temps pour interagir avec l’outil de façon plus étendue.